Pelatihan Kader Kesehatan untuk Penemuan Penderita Suspek Tuberkulosis - Wahyuni, Chatarina Umbul; Artanti, Kurnia Dwi (Kesmas, 2013)
Di Indonesia, kasus tuberkulosis (TB) yang dilaporkan pada tahun 2011 ter- deteksi lebih dari 70% dan cenderung terus meningkat. Di Kota Surabaya, cakupan penemuan penderita adalah sekitar 49,52% dengan jumlah suspek TB sebanyak 4.402 orang hingga tahun 2011. Keterlibatan masyarakat dalam penanggulangan TB tersebut sesuai dengan Kerangka Kerja Strategi Penanggulangan TB 2006-2010. Masyarakat berpeluang untuk berperan dalam penanggulangan TB, sumber daya di masyarakat dimanfaatkan untuk meningkatkan derajat kesehatan dan mengubah perilaku masyarakat. Penelitian ini bertujuan mengetahui pengaruh pelatihan terhadap pengetahuan kader kesehatan dalam penemuan suspek TB. Penelitian kuantitatif ini menggunakan rancangan studi kuasi eksperimental kelompok kontrol non-ekuivalen. Perlakuan pelatihan program pengendalian berupa penemuan suspek TB. Populasi penelitian adalah ibu rumah tangga di wilayah kerja Puskesmas Mojo di Kota Surabaya dengan jumlah sampel 90 ibu rumah tangga berumur rata-rata 48 tahun, tingkat pendidikan terbanyak adalah tamat SMA (58,9%). Setelah pelatihan, pengetahuan kader tentang penemuan suspek TB meningkat dari 67 (74,4%) menjadi 89 (98,9%). Perlu implementasi untuk melihat kemampuan kader menerapkan pengetahuan yang diperoleh dalam menemukan suspek penderita TB dengan pen- dampingan dan monitoring kader. Progress reports current situation of tuberculosis (TB) in Indonesia in 2011 showed Case Detection Rate (CDR) of over 70% and showed an increase from year to year. While the city of Surabaya figures coverage discovery Patients up to 2011 amounted to 49.52% with the number of 4,402 people suspected. Community involvement in TB control in accordance with the Tuberculosis Control Strategy Framework 2006-2010. The opportunities as well as public opportunities to participate in TB control to make the resources available in the community should be utilized to improve health status and change people’s behavior as a factor influencing health status. This study aimed to determine the effect of training on the knowledge of health cadres in the discovery of suspected tuberculosis. This study uses quantitative methods to the design of a Quasi Nonequivalent Experimental Control Group Design. Treatment will be given in the form of training on tuberculosis control program in the discovery suspected tuberculosis. The population in this study was a housewife in Puskesmas Mojo working in the city of Surabaya. Large sample taken as many as 90 respondents. Characteristics housewife with average age 48 years, female gender, and education all most 31.1%. Improvement occurred knowledge of 67 (74.4 %) health workers who have good knowledge before training to 89 (98.9 %). Based on the results of this study concluded increased knowledge of health workers after training in the discovery of suspected tuberculosis. Further implementation is needed to see the ability of the implementing cadres who have acquired knowledge in finding patients with suspected tuberculosis in the surrounding environment. In its application may be made to the guidance and monitoring of health cadres in the process of discovery with suspected tuberculosis.